2014
DOI: 10.2985/026.019.0106
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition ofOpuntia sulphureaG. Don Cladodes

Abstract: by non-industrialized cultures in the arid regions of the Americas for thousands of years (Ervin 2012). In its native range, Opuntia species also provide food for innumerable herbivores (Mellink and Riojas-López 2002), which underscores the ecological importance of the genus. In other areas, Opuntia species have been introduced into wildlands and pastures with non-desirable consequences due to the extensive invasion of escaped plants (Cronk and Fuller

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
19
2
Order By: Relevance
“…In fact, in Drosophila , correlations between the circadian clock and development time have been observed, with the latter depending in turn on the substrate quality (Walkiewicz & Stern, ; Yadav & Sharma, ). In the present case, O. sulphurea is a cactus host richer in sugar and fat content respect to T. terscheckii (Padro & Soto, ; Carreira et al ., ), which also harbors higher diversity of cactophilic microorganisms and yeasts in its necrotic tissues (Mongiardino Koch et al ., ). Therefore, the experimental substrates are nutritionally different and could be a key factor conditioning the time spent in pupal stage, thus affecting ET as we know it affects development time (Soto et al ., ; Soto et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in Drosophila , correlations between the circadian clock and development time have been observed, with the latter depending in turn on the substrate quality (Walkiewicz & Stern, ; Yadav & Sharma, ). In the present case, O. sulphurea is a cactus host richer in sugar and fat content respect to T. terscheckii (Padro & Soto, ; Carreira et al ., ), which also harbors higher diversity of cactophilic microorganisms and yeasts in its necrotic tissues (Mongiardino Koch et al ., ). Therefore, the experimental substrates are nutritionally different and could be a key factor conditioning the time spent in pupal stage, thus affecting ET as we know it affects development time (Soto et al ., ; Soto et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent nutritional studies of both cacti revealed that O. sulphurea has slightly more free sugars (although lower than other Opuntia) and total fat, while T. terscheckii has a richer composition of fatty acids Carreira et al 2014).…”
Section: The Cactus Hosts Are Chemically Differentmentioning
confidence: 99%
“…Although prickly pears (genus Opuntia ) are its main natural hosts, D. buzzatii can exploit columnar cacti of the genera Trichocereus and Cereus as secondary hosts (Barker, ; Soto et al ., ). Recent studies suggest the presence of alkaloids as the main chemical difference between O. sulphurea and Trichocereus terschekii (Hasson et al ., ; Padró & Soto, ; Carreira et al ., ), two of the most important D. buzzatii host plants in Argentina. Actually, T. terscheckii is especially rich in phenethylamines alkaloids (Reti & Castrillon, ; Corio et al ., ), and recent studies showed that an alkaloid fraction causes detrimental effects by impairing viability and decreasing body size (Corio et al ., ).…”
Section: Introductionmentioning
confidence: 99%